Serum ischemia modified albumin level and its relationship with the thiol/disulfide balance in placenta percreta patients. (17th November 2018) - Uyanikoglu, Hacer; Sak, Muhammet Erdal; Tatli, Faik; Hilali, Nese Gul; Sak, Sibel; Incebiyik, Adnan; Barut, Mert Ulas; Erel, Ozcan; Gonel, Ataman
Abstract: The pathogenesis of placenta percreta (PP) is not very well known. This study was designed to analyse the oxidative stress (OS), the thiol/disulphide balance, and ischaemia-modified albumin (IMA) the women with PP. The study included 38 pregnant women with PP and 40 similarly aged healthy pregnant women in their third trimester of gestation. We measured the IMA, native and total thiols, and disulphide concentrations in the maternal sera of all of the participating women. The IMA levels were higher and the native and total thiols were lower in the PP group than in the control group. However, there was no statistical significance with respect to the thiol/disulphide balance between the two groups. The results of this study suggest that an increase in the ischaemia and OS and a decrease in the antioxidant status may contribute to the pathogenesis of PP. Impact statement: What is already known on this subject? Placenta percreta (PP) is a serious complication of pregnancy. Although there are several studies investigating the pathophysiological mechanism of PP, whether the pathology results from a lack of decidua or from the over-invasiveness of trophoblasts remains controversial. The pathology of PP is poorly understood. What do the results of this study add? This prospective study has shown an increased ischaemia modified albumin (IMA) and a decreased antioxidant capacity in the patients with placenta percreta. The results from 38 women with PP suggest that the serum concentrations of IMA and the oxidative stress parameters may be able to predict PP in cases of uncertainty. What are the implications of these findings for clinical practice and/or further research? The implication of these findings shed light on understanding the pathogenesis of PP for further research.